Development of micropropagation protocol for production of elite blueberry planting material in Kazakhstan - Rymkhanova, N.K.; Manapkanova, U.A.; Mikhailenko, N.V.; Kushnarenko, S.V. (Karagandy University of the name of academician E.A. Buketov, 2025)
This study presents an optimized protocol for micropropagation of commercially valuable highbush blueberry (Vaccinium corymbosum L.) varieties adapted to climatic conditions of Kazakhstan. An effective explant surface disinfection technique was established, providing a high percentage of aseptic plants. Various nutrient media with auxins (IBA, IAA) and cytokinins (zeatin, BAP) were evaluated for shoot proliferation and rooting. The optimal medium for micropropagation was identified as Woodt Plant Medium (WPM) with a double concentration of Ca(NO3)2, 2 mg/L zeatin, 30 g/L sucrose, 3.5 g/L agar, 1.5 g/L gelzan, pH 5.2. The most effective shoot rooting was achieved on half-strength WPM medium with 0.5 mg/L IBA, 30 g/L sucrose, and vermiculite (pH 5.2). In vitro rooted plants were successfully acclimatized to soil conditions by gradually reducing humidity in a controlled greenhouse environment at 20‒23 °C. The developed micropropagation protocol enables rapid and mass propagation of elite blueberry varieties, ensuring genetic stability and minimizing the risk of pathogen infection. The results obtained contribute to the development of industrial blueberry cultivation in Kazakhstan and promote of modern biotechnological approaches in berry crop production.
Keywords: in vitro rooting; micropropagation; Vaccinium corymbosum L.; blueberry